Prognostic Determinants of Coronary Atherosclerosis in Stable Ischemic Heart Disease: Anatomy, Physiology, or Morphology?. Issue 2 (8th July 2016) - Ahmadi, Amir; Stone, Gregg W.; Leipsic, Jonathon; Shaw, Leslee J.; Villines, Todd C.; Kern, Morton J.; Hecht, Harvey; Erlinge, David; Ben-Yehuda, Ori; Maehara, Akiko; Arbustini, Eloisa; Serruys, Patrick; et al.
Abstract : Risk stratification in patients with stable ischemic heart disease is essential to guide treatment decisions. In this regard, whether coronary anatomy, physiology, or plaque morphology is the best determinant of prognosis (and driver an effective therapeutic risk reduction) remains one of the greatest ongoing debates in cardiology. In the present report, we review the evidence for each of these characteristics and explore potential algorithms that may enable a practical diagnostic and therapeutic strategy for the management of patients with stable ischemic heart disease.